Physiological and biochemical responses of nile tilapia (Oreochromis niloticus) to acute trichlorfon exposure - Cardoso, Israel Luz [UNESP]; Soares, Michelly Pereira [UNESP]; De Angelis, Carolina [UNESP]; Ferri, Giovanni Henrique; Ishikawa, Marcia Mayumi; Jonsson, Claudio Martin; Rantin, Francisco Tadeu [UNESP]; Sampaio, Fernanda Garcia (My University, 2020)
Trichlorfon [TCF] is an organophosphate compound used to eliminate or control a variety of parasites in farmed fish. The physiological and biochemical responses of juvenile Nile tilapia were studied after 96 hours of exposure to TCF. The experiment was conducted randomly with two treatments: control and TCF (0.5 mg L-1). No mortality or changes in hematological profile were recorded for the fish. On the other hand, we found that TCF exposure caused behavioral, metabolic and hormonal changes that modified the response patterns of the immune and enzymatic defense system in muscle and liver tissues. Increased plasma cortisol and glucose combined with the reduction of acetylcholinesterase activity in muscle and liver tissue after 96-h of TCF exposure indicates chemical stress. In response to this harmful situation, we observed changes in the immune system that lead to an increased number of leukocytes, thrombocytes, monocytes, lysozyme and leukocyte respiratory burst activity. Furthermore, we associate the increased activity of glutathione-S-transferase in liver tissue as a strategy fish use to combat the effects of TCF. Thus, we conclude that TCF affects the physiologic parameters of Nile tilapia, which can generate irreversible situations of recovery of the clinical condition. Such fact highlights the need to search for new compounds that could replace TCF, that have no or few adverse effects on fish species.
Keywords: Aquaculture; Chemotherapy; Toxicology; Trichlorfon